Maternal and Environmental Factors Associated with Low Birth Weight: A Systematic Literature Review - Ayu Yuliani Sekriptini; Oktia Woro Kasmini Handayani; Haryono Haryono (Lembaga Publikasi Ilmiah Nusantara, 2026)
This study aims to examine maternal and environmental factors associated with low birth weight through a systematic literature review. The review followed the PRISMA framework to ensure a structured, transparent process for identification, screening, eligibility, and inclusion. Literature searching was conducted using the Directory of Open Access Journals (DOAJ) for studies published between 2022 and 2026. A total of 320 records were identified; after duplicate removal, 308 were screened, and 10 studies were included in the final synthesis. The findings indicate that low birth weight is a multidimensional outcome shaped by the interaction of maternal and environmental determinants. The most consistent maternal factors include preeclampsia, anemia, poor nutritional status, inadequate micronutrient intake, adverse reproductive history, and unhealthy lifestyle behaviors. Environmental determinants such as air pollution, household smoke exposure, solid fuel use, and poor housing conditions were also strongly associated with low birth weight. This review highlights that isolated factors cannot explain low birth weight; rather, it arises from cumulative biological and environmental vulnerabilities. The study contributes to strengthening integrative understanding and supports the development of comprehensive maternal and environmental health interventions.